Down under - Reynolds, Jan, 1956- (San Diego : Harcourt Brace Jovanovich, 1992)
Examines the vanishing culture of the Tiwi tribe, aborigines who live on a small island off the coast of Australia.
Keywords: Tiwi (Australian people) -- Juvenile literature; Tiwi (Australian people); Australian aborigines